Numerical-probabilistic assessment of tempered glass failure based on the generalised local model characterised by annealed plates. (15th October 2022) - Iglesias, A.; Muniz-Calvente, M.; Fernández-Canteli, A.; Llavori, I.; Martinez-Agirre, M.; Esnaola, J.A.
Abstract: Large-scale experimental programmes become unavoidable to characterise the fracture behaviour of glass. Additionally, if non-uniform residual stresses are to be considered, the total effort required increases significantly. In this work, the primary failure cumulative distribution function (PFCDF) is derived from experimental annealed glass data. In this way, a novel methodology based on the characterisation of annealed glass to assess the failure of pre-stressed glass components is presented. Similarly, a joint evaluation of annealed and tempered glass is performed, thereby ensuring a higher reliability in the derivation of the PFCDF, which results in an average error below 10%. Graphical abstract: Highlights: Probabilistic fracture prediction of tempered glass from annealed glass data. Reliable transferability of fracture results independent of residual stress pattern. Enhanced reliability in fracture predictions for tempered and annealed glass data. Basis for ad hoc heat treatment process design early in the production cycle.